2013
DOI: 10.1037/per0000020
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal examination of emotion regulation difficulties as a function of co-occurring avoidant personality disorder among women with borderline personality disorder.

Abstract: Despite a robust association between borderline personality disorder (BPD) and emotion dysregulation, evidence of within-BPD group differences in emotion regulation (ER) difficulties highlights the need to examine factors that increase the risk for ER difficulties within BPD. One factor that warrants consideration is co-occurring avoidant personality disorder (AVPD), the presence of which is associated with worse outcomes in and outside of BPD and theorized to interfere with adaptive ER. Thus, this study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 72 publications
(120 reference statements)
1
55
1
2
Order By: Relevance
“…Women with BPD were divided into two groups: those with comorbid avoidant personality disorder (AVPD), and those without comorbid AVPD. The authors found no significant group differences comparing BPD with AVPD, BPD without AVPD, and controls on HF HRV at baseline and HRV during the low-stress section of the distress tolerance taskcausing them to conclude that without emotional distress, BPD participants respond similarly to normal controls (Gratz et al, 2013), based on a significant difference during a stress task. The authors reported that while BPD patients without AVPD and controls displayed a slight increase in HF-HRV, BPD patients with AVPD displayed a decrease in HF-HRV reactivity (Gratz et al, 2013).…”
Section: Summaries Of Included Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Women with BPD were divided into two groups: those with comorbid avoidant personality disorder (AVPD), and those without comorbid AVPD. The authors found no significant group differences comparing BPD with AVPD, BPD without AVPD, and controls on HF HRV at baseline and HRV during the low-stress section of the distress tolerance taskcausing them to conclude that without emotional distress, BPD participants respond similarly to normal controls (Gratz et al, 2013), based on a significant difference during a stress task. The authors reported that while BPD patients without AVPD and controls displayed a slight increase in HF-HRV, BPD patients with AVPD displayed a decrease in HF-HRV reactivity (Gratz et al, 2013).…”
Section: Summaries Of Included Studiesmentioning
confidence: 97%
“…Another study was excluded because it didn't report a measure of vmHRV (Battaglia et al, 1995). Following exclusions, a total of 5 studies (Austin et al, 2007;Dixon-Gordon et al, 2011;Gratz et al, 2013;Kuo and Linehan, 2009;Weinberg et al, 2009) were eligible for inclusion in the meta-analysis. These studies are summarized in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, independent samples of perceivers rated the targets on one of several behaviorallyand clinically-relevant characteristics found to typically associate with BPD in previous research: depression, anxiety, emotional instability, social avoidance (tested as ''introversion''), and impulsivity (Glenn and Klonsky 2009;Gratz et al 2013;Gunderson 2010;Koenigsberg et al 2002;Trull et al 2008;Zimmerman and Mattia 1999).…”
Section: Study 2amentioning
confidence: 99%